The Ecology of Perth’s Urban Reptiles Using a Snake and Skink as Models - Wolfe, Ashleigh Katherine (Curtin University, 2017)
Urbanisation presents unique challenges for wildlife and promotes human-wildlife interactions. The effects if urbanisation on reptiles has been little studied. I explored the life history traits correlated with urban adaptation for reptiles, and investigated how urbanisation affects diet, spatial use, and behavioural responses of two reptiles in south-west Western Australia: dugite (Pseudonaja affinis, Elapidae) and bobtail skink (Tiliqua r. rugosa, Scincidae). I also investigated the attitudes and perceptions of the general public towards these species.